The Presentation Location of the Reference Stimuli Affects the Left-Side Bias in the Processing of Faces and Chinese Characters - Li, Chenglin; Cao, Xiaohua (Frontiers in Psychology, 2017)
For faces and Chinese characters, a left-side processing bias, in which observers rely more heavily on information conveyed by the left side of stimuli than the right side of stimuli, has been frequently reported in previous studies. However, it remains unclear whether this left-side bias effect is modulated by the reference stimuli's location. The present study adopted the chimeric stimuli task to investigate the influence of the presentation location of the reference stimuli on the left-side bias in face and Chinese character processing. The results demonstrated that when a reference face was presented in the left visual field of its chimeric images, which are centrally presented, the participants showed a preference higher than the no-bias threshold for the left chimeric face; this effect, however, was not observed in the right visual field. This finding indicates that the left-side bias effect in face processing is stronger when the reference face is in the left visual field. In contrast, the left-side bias was observed in Chinese character processing when the reference Chinese character was presented in either the left or right visual field. Together, these findings suggest that although faces and Chinese characters both have a left-side processing bias, the underlying neural mechanisms of this left-side bias might be different.